Penerapan Metode Moora Dalam Menentukan Pegawai Terbaik Pada Fakultas Ekonomi Dan Bisnis Universitas Bengkulu - Muhammad David Bekam; Dimas Aulia Trianggana; Ahmad Arif Alfarisy (UNIVED Press, 2026)
Determining the best employees is an effort to provide appreciation while also motivating employee performance within the Faculty of Economics and Business at Universitas Bengkulu. This study applies the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method to provide recommendations for the best employees in an objective, systematic, and data-driven manner. The method is used because it can process data based on relevant criteria and produce consistent rankings. The assessment process involves collecting data from 11 employees based on registration data for the year 2024, which is then processed using the MOORA method to obtain rankings from highest to lowest. The best employee recommendations are established for the top three rankings. Based on the calculations, the three best employees identified are Tiharman, SH, Sutomo, S.Sos, and Dahril Alpansi, SH. The results of this research are expected to serve as a reference for the faculty in determining the best employees more accurately and transparently each year